2012
DOI: 10.1017/s0007114512002358
|View full text |Cite
|
Sign up to set email alerts
|

Role of specific dietary amino acids in clinical conditions

Abstract: In a variety of chronic and acute disease states, alterations in protein synthesis, breakdown and protein turnover rates occur that are related to the loss of body protein and skeletal muscle wasting. A key observation is the stimulation of protein breakdown in muscle and the stimulation of protein synthesis in the splanchnic area; mainly liver. An altered splanchnic extraction of amino acids as well as an anabolic resistance to dietary protein, related to stress, disuse and aging play a key role in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 84 publications
1
41
0
3
Order By: Relevance
“…However, consuming a protein source or protein blend with a low leucine content will likely be of greater impact on stimulating postprandial muscle protein accretion in older and more clinically compromised populations. As mentioned, these individuals require greater amounts of leucine (>2.5-3g) to maximize postprandial MPS rates (50,91).…”
Section: Strategies To Augment the Anabolic Properties Of Plant-basedmentioning
confidence: 96%
See 1 more Smart Citation
“…However, consuming a protein source or protein blend with a low leucine content will likely be of greater impact on stimulating postprandial muscle protein accretion in older and more clinically compromised populations. As mentioned, these individuals require greater amounts of leucine (>2.5-3g) to maximize postprandial MPS rates (50,91).…”
Section: Strategies To Augment the Anabolic Properties Of Plant-basedmentioning
confidence: 96%
“…The leucine content of a meal appears to be of fundamental importance to postprandial stimulation of MPS, especially in older populations (50) and in more clinically compromised patient groups (91). Previously, Rieu et al (72) found that approximately doubling the leucine content of mixed meals increased MPS rates in older individuals.…”
Section: Strategies To Augment the Anabolic Properties Of Plant-basedmentioning
confidence: 99%
“…These include amino acids, tRNA, adenosine polyphosphate such as Ap4A, and aminoacyl-adenylates, which can control cell proliferation, translation, transcription, and apoptosis [23,40,[154][155][156][157]. The regulation of these factors and their functional relationship with ARSN will be a promising theme with regard to cancer.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the past years, a strong theoretical rationale has been demonstrated for the use of amino acid mixtures in populations suffering from muscle wasting (35). Amino acids are the main nutrients responsible for acute stimulation of muscle protein synthesis, and essential amino acids (EAA) are solely responsible for the amino acid induced stimulation of muscle protein anabolism in healthy individuals and insulin-resistant states (36).…”
Section: Introductionmentioning
confidence: 99%